Effect Of In-Situ Vulcanization Of Styrene Modified Natural Rubber In Adhesive And Rubber Toughened Polystyrene Applications - Neoh , Siew Bee (2010)

(untitled)
In this research, establishment of vulcanization formulation of styrene modified natural rubber ( SNR ) vulcanizates by using in situ vulcanization technique was investigate. The synthesis of SNR was prepared through emulsion polymerization. Deproteinized natural rubber latex (DPNR) was grafted with styrene monomer with the addition of ammonium persulfate as initiator. SNR vulcanizate was prepared with different vulcanization methods and vulcanization agents. The first stage of the work involved in established the emulsion polymerization of SNR with ratio of styrene monomer and DPNR ratio 25%: 75%. For adhesive application, the effect of three pre-vulcanization systems, conventional vulcanization (CV), semi-efficient vulcanization (semi-EV), and efficient vulcanization (EV) on tensile properties of SNR pre-vulcanizates were observed. The semi-EV vulcanization system showed suitable properties as SNR pre-vulcanizates adhesives. It showed similar trend in elongation at break (EB) compared to CV system with low tensile strength (TS). The effect of pH modification on semi-EV pre-vulcanized system showed the SNR with good anchorage ability at pH 12 suitable for adhesive application. For rubber toughened material application, in situ vulcanization process with sulfur as crosslinking agent had improved the impact strength of the PS/ SNR vulcanizates.